Achromobacter Species Isolated from Cystic Fibrosis Patients Reveal Distinctly Different Biofilm Morphotypes - Signe M. Nielsen; Niels Nørskov-Lauritsen; Thomas Bjarnsholt; Rikke L. Meyer (Microorganisms, 2016)
Achromobacter species have attracted attention as emerging pathogens in cystic fibrosis. The clinical significance of Achromobacter infection is not yet fully elucidated; however, their intrinsic resistance to antimicrobials and ability to form biofilms renders them capable of establishing long-term chronic infections. Still, many aspects of Achromobacter biofilm formation remain uncharacterized. In this study, we characterized biofilm formation in clinical isolates of Achromobacter and investigated the effect of challenging the biofilm with antimicrobials and/or enzymes targeting the extracellular matrix. In vitro biofilm growth and subsequent visualization by confocal microscopy revealed distinctly different biofilm morphotypes: a surface-attached biofilm morphotype of small aggregates and an unattached biofilm morphotype of large suspended aggregates. Aggregates consistent with our in vitro findings were visualized in sputum samples from cystic fibrosis patients using an Achromobacter specific peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) probe, confirming the presence of Achromobacter biofilms in the CF lung. High antibiotic tolerance was associated with the biofilm phenotype, and biocidal antibiotic concentrations were up to 1000 fold higher than for planktonic cultures. Treatment with DNase or subtilisin partially dispersed the biofilm and reduced the tolerance to specific antimicrobials, paving the way for further research into using dispersal mechanisms to improve treatment strategies.